Effect of video on satisfaction and self-confidence in simulation training: a randomized clinical trial - Lissette Lucrecia Monge Abarca; Alba Lúcia Bottura Leite de Barros; Rui Carlos Negrão Baptista; Ruth Ester Assayag Batista; Juliana de Lima Lopes (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify the effect on satisfaction and self-confidence of undergraduate nursing students after using a validated bed bath video during the simulation. Methods: blinded parallel randomized clinical trial. Participants were allocated to the control group (simulation with tutor) or intervention (simulation with video). After the interventions, the Student Satisfaction and Self Confidence with Learning Scale was used to assess satisfaction and self-confidence. The study was approved by the Ethics Committee and Brazilian Registry of Clinical Trials. Mann Whitney, Fisher Exact and Student t statistical tests were used. A significance level of 5% was adopted. Results: fifty eight students (30, control; and 28, intervention) were evaluated. There was no significant difference between the groups regarding satisfaction (p=0.832) and self-confidence (p>0.999). Conclusions: satisfaction and self-confidence were similar between the groups, and the two strategies could be used in the simulated practice of bed bathing.